Upaya Pencegahan Infeksi Sistem Reproduksi Pada Remaja Putri Melalui Edukasi Menstrual Hygiene Di SMP Negeri 3 Kalasan, Yogyakarta - Hutasoit, Masta; Purnamaningsih, Nur ’Aini; Trisetiyaningsih, Yanita; Susanti, Dwi (Universitas Negeri Gorontalo, 2024)
Adolescent girls who experience menstruation as a sign of the onset of puberty certainly need important information in carrying out hygiene behaviors during menstruation. Menstrual hygiene is an action taken to care for and maintain cleanliness in the feminine area, especially during menstruation. This is done to prevent infections in the reproductive tract. Personal hygiene during menstruation needs to be considered, especially in adolescence. Many teenagers do not pay attention to personal hygiene during menstruation and show a negative attitude, and consider it taboo so they do not seek information. Adolescent women's knowledge about Menstrual Hygiene is needed as a preventive effort when the menstrual cycle occurs in adolescent girls. Young women's knowledge can be obtained by providing health counseling. This community service aims to increase students' knowledge about the cleanliness of the feminine area. The results of this service are known to increase the understanding of adolescent girls in improving hygiene during menstruation (menstrual hygiene). The average initial knowledge for menstrual hygiene is 79% with a minimum score of 30 and a maximum of 100. After the test post, the average score of knowledge increased to 98.15% (minimum score of 80 and maximum score of 100). In addition to menstrual hygiene, education about puberty was also carried out with an average initial score of 65.2% (50-100) and an average test post of 94.53% (75-100%). During the education, participants seemed enthusiastic by being able to answer questions from service members. The conclusion of this service is so that young women can practice the knowledge gained to maintain personal hygiene and feminine hygiene during the menstrual cycle to avoid reproductive infections.